An Outbreak of neonatal diarrhea associated to rotavirus type C - Aspitia, Carolina Gabriela (2020)
Neonatal diarrhea is one of the main causes of preweaning mortality worldwide. Diarrhea is the result of the combination of several factors, including infectious agents, host immunity, environment and management procedures (7). Newborn piglets are susceptible to infection by several enteric microorganisms, including virus, bacteria and protozoans (7). Among viruses, in Argentina porcine rotaviruses (PoRV) groups A, B and C and transmissible gastroenteritis coronavirus (TGEV) has been described associated with subclinical or severely diarrheic outbreaks (4,6). Rotaviruses have a dsRNA genome that contains 11 segments. They are classified into 10 serogroups (A-J) through cross-reactivity of antigens on the VP6 protein that makes up the intermediate layer of the tripe-layer capsid shell of the virus (7). Rotavirus group A, B and C are ubiquitous in swine population; however, group A is the most extensively found on neonatal diarrhea. We perform a multidisciplinary approach in order to clarify an outbreak of a neonatal diarrhea.